The Location of the Center of Pressure on the Starting Block Is Related to Sprint Start Performance - Nagahara, Ryu; Ohshima, Yuji (Frontiers in Sports and Active Living, 2019)
Force application locations (i.e. center of pressure [COP]) on the block surface are not necessarily the same for individuals even if the same block locations and angles are used. The purpose of this study was to examine the association of block clearance performance with COP location on the starting block surface. Twenty-one male sprinters performed 60-m sprints from the starting blocks, during which the ground reaction forces (GRFs) on the starting blocks were recorded using two force platforms. Using a previously validated method, changes in COP location on the block surface during the block clearance for each block was calculated from the marker coordinates on the block surface, GRF signals and moment data around the center of the force platform at the ground level. Moreover, average horizontal external power (AHEP), which was considered the key performance criterion, was computed. Statistical parametric mapping (SPM) 1D linear regressions were used to test relationships between AHEP and COP location curves in the anteroposterior and vertical directions. The COP for both legs moved backward and upward (0.042 and 0.042 m for the front block and 0.030 and 0.034 m for the rear block) at first and then forward and downward (0.113 and 0.094 m for the front block and 0.095 and 0.087 m for the rear block) toward the toe-off. Based on SPM results, AHEP was correlated with front block anteroposterior and vertical COP locations from 12.9% to 20.8% and from 10.4% to 22.2% of the force production phase, respectively, while it was correlated with rear block vertical COP location from 31.9% to 37.4% of the force production phase. In conclusion, the current results demonstrate that, regardless of the starting block location and angle, better sprint start performance is accomplished with a higher and more to the rear COP on the starting block surface, when COP is located close to heel during the middle phase of the block clearance. The fact that the COP location is related to sprint start performance will be useful for sprinters and coaches who intend to improve sprint start performance.